Implementasi Metode Latihan Kombinasi Permainan Target Untuk Meningkatkan Hasil Belajar PJOK Materi Bola Basket Pada Murid Kelas XI SMA Negeri 1 Kerambitan - I Gede Anom Aditya Saputra; I Putu Panca Adi; Hendra Mashuri (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan Undiksha, 2026)
This study aimed to improve learning outcomes in Physical Education, Sports, and Health (PJOK), particularly basketball shooting skills, through the implementation of the Combined Target Game Training Method among eleventh-grade students at SMA Negeri 1 Kerambitan in the 2025/2026 academic year. This study employed Classroom Action Research conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. The research subjects were 22 eleventh-grade students of SMA Negeri 1 Kerambitan. The study was conducted in four meetings, consisting of two meetings in Cycle I and two meetings in Cycle II. Learning outcomes were assessed in three domains: attitude, knowledge, and skills. The data were analyzed descriptively based on the percentage of learning mastery. The results showed an improvement in students’ learning outcomes after the implementation of the Combined Target Game Training Method. In Cycle I, mastery in the attitude domain reached 54.5%, knowledge reached 40.9%, and skills reached 72.7%. In Cycle II, mastery increased to 81.8% in attitude, 54.5% in knowledge, and 100% in skills. These improvements indicate that combining shooting practice with target games provides students with opportunities to repeatedly practice movements through active, engaging, and goal-oriented learning activities. Therefore, it can be concluded that the implementation of the Combined Target Game Training Method can improve students’ learning outcomes in basketball shooting among eleventh-grade students at SMA Negeri 1 Kerambitan. Keywords: combined training, target games, learning outcomes, shooting, basketball